Estudio de factibilidad para la creación de una empresa comercializadora de productos cosméticos y lencería personalizada en la ciudad de Bogotá D.C. (2020)
The purpose of this feasibility study is to determine the viability of creating a marketer of cosmetic products and lingerie through an online store in the city of Bogotá D.C. First of all, an evaluation of the environmental conditions was made, using different tools such as: the PESTEL analysis (political, economic, social, technological, environmental and legal) from Colombia and also from Bogotá D.C., analysis of Porter’s 5 forces, analysis of the sector and subsector and to conclude a DOFA matrix. Then, a market study was developed, in which, it was possible to determine the target market and also, a projection of the demand was made for the next 5 years taking in count products and customers. Finally after that, an analysis of the competitors was made, together with the development of the marketing mix.